A postoperative anti-adhesion barrier based on photoinduced imine-crosslinking hydrogel with tissue-adhesive ability. (15th October 2017) - Yang, Yunlong; Liu, Xiaolin; Li, Yan; Wang, Yang; Bao, Chunyan; Chen, Yunfeng; Lin, Qiuning; Zhu, Linyong
Graphical abstract: Abstract: Postoperative adhesion is a serious complication that can further lead to morbidity and/or mortality. Polymer anti-adhesion barrier material provides an effective precaution to reduce the probability of postoperative adhesion. Clinical application requires these materials to be easily handled, biocompatible, biodegradable, and most importantly tissue adherent to provide target sites with reliable isolation. However, currently there is nearly no polymer barrier material that can fully satisfy these requirements. In this study, based on the photoinduced imine-crosslinking (PIC) reaction, we had developed a photo-crosslinking hydrogel (CNG hydrogel) that composed of o-nitrobenzyl alcohol (NB) modified carboxymethyl cellulose (CMC-NB) and glycol chitosan (GC) as an anti-adhesion barrier material. Under light irradiation, CMC-NB generated aldehyde groups which subsequently reacted with amino groups distributed on GC or tissue surface to form a hydrogel barrier that covalently attached to tissue surface. Rheological analysis demonstrated that CNG hydrogel (30 mg/mL polymer content) could be formed in 30 s upon light irradiation. Tissue adhesive tests showed that the tissue adhesive strength of CNG hydrogel (30 mg/mL) was about 8.32 kPa–24.65 kPa which increased with increasing CMC-NB content in CNG hydrogel. Toxicity evaluation by L929 cells demonstrated that CNG hydrogel was cytocompatible. Furthermore, sidewall defect-cecum abrasion model of rat was employed to evaluate the postoperative anti-adhesion efficacy of CNG hydrogel. And a significantly reduction of tissue adhesion (20% samples with low score adhesion) was found in CNG hydrogel treated group, compared with control group (100% samples with high score adhesion). In addition, CNG hydrogel could be degraded in nearly 14 days and showed no side effect on wound healing. These findings indicated that CNG hydrogel can effectively expanded the clinical treatments of postoperative tissue adhesion. Statement of Significance: In this study, a tissue adhesive photo-crosslinking hydrogel (CNG) was developed based on photo-induced imine crosslinking reaction (PIC) for postoperative anti-adhesion. CNG hydrogel showed the features of easy and convenient operation, fast and controllable gelation, suitable gel strength, good biocompatibility, and most importantly strong tissue adhesiveness. Therefore, it shows very high performance to prevent postoperative tissue adhesion. Overall, our study provides a more suitable hydrogel barrier material that can overcome the shortcomings of current barriers for clinical postoperative anti-adhesion.